2013
DOI: 10.4100/jhse.2013.83.04
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural contrasts in motor fitness components of youngster footballers in West Bengal, India

Abstract: Das, P. & Chatterjee, P. (2013). Urban-rural contrasts in motor fitness components of youngster footballers in West Bengal, India. J. Hum. Sport Exerc., 8(3), pp.797-805. In the present world sport and exercise should be well-matched with the surroundings and public healthiness. This study aims to examine whether urban-rural environment have any impact on motor fitness components of footballers as well as sedentary boys of the age group 14 to 16 years. The sample consisted of 60 football players (30 urban and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
2
9
0
3
Order By: Relevance
“…A comparison of physical education (PE) classes conducted indoors and outdoors also showed greater improvement in motor abilities with outdoor PE, although class time was similar for indoor and outdoor PE [53]. Higher PA levels during childhood, along with a greater amount of PA accumulated outdoors, can also explain higher physical fitness levels in rural adolescents as compared with their urban peers [2,54] despite their lower PA levels, particularly during the weekend [2,31,55]. A potential explanation for lower PA in rural adolescents could be a greater contribution of organized sports to total PA during adolescence, while free play becomes less important at older ages [56].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of physical education (PE) classes conducted indoors and outdoors also showed greater improvement in motor abilities with outdoor PE, although class time was similar for indoor and outdoor PE [53]. Higher PA levels during childhood, along with a greater amount of PA accumulated outdoors, can also explain higher physical fitness levels in rural adolescents as compared with their urban peers [2,54] despite their lower PA levels, particularly during the weekend [2,31,55]. A potential explanation for lower PA in rural adolescents could be a greater contribution of organized sports to total PA during adolescence, while free play becomes less important at older ages [56].…”
Section: Discussionmentioning
confidence: 99%
“…Con respecto al análisis del componente morfológico, los resultados de este trabajo mostraron que los escolares que residen en áreas urbanas tienen un mayor peso (p < 0,001), talla (p < 0,001), e IMC (p < 0,05), lo que concuerda con lo observado en otros trabajos realizados en poblaciones rurales y urbanas de los EE.UU, la India, y España (Das & Chatterjee, 2013;De la Cruz-Sánchez et al, 2013;Joens-Martre et al, 2008;McMurray et al, 1996). Además de poseer un mayor IMC que sus semejantes de zonas rurales, los escolares de zonas urbanas tuvieron un mejor desempeño en las pruebas de CF.…”
Section: Discussionunclassified
“…Das & Chatterjee (2013), en un estudio realizado con escolares pertenecientes a la provincia de Bengala (India), sí mostraron diferencias estadísticamente signiicativas en las pruebas utilizadas para medir la velocidad (carrera de 50m) y la agilidad (carreta 5 x 10m) a favor de los escolares de zonas rurales, lo que concuerda con lo encontrado por De la Cruz-Sánchez et al (2013) en escolares españoles.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A study in Japan demonstrated that the children from rural areas had better endurance ability https://www.indjst.org/ than the children in urban areas from Japan (14) while, in a cross-sectional survey of the growth of urban and rural 'Cape Colored' schoolchildren: Anthropometry and functional tests reported that the children from rural areas in South Africa (15) were found to have significantly lower grip strength than urban children, but no significant differences were reported among rural and urban children in neuromuscular reaction time and pulse rate. In India, the results of the various studies show that rural children were better in anthropometric characteristics and physical fitness than urban children (16)(17)(18)(19)(20) .…”
Section: Discussionmentioning
confidence: 99%